Genome-wide transcriptional changes triggered by water deficit on a drought-tolerant common bean cultivar - Josefat Gregorio Jorge; Miguel Angel Villalobos-López; Karen Lizeth Chavarría-Alvarado; Selma Ríos-Meléndez; Melina López-Meyer; Analilia Arroyo-Becerra (BMC Plant Biology, 2020)
Abstract Background Common bean (Phaseolus vulgaris L.) is a relevant crop cultivated over the world, largely in water insufficiency vulnerable areas. Since drought is the main environmental factor restraining worldwide crop production, efforts have been invested to amend drought tolerance in commercial common bean varieties. However, scarce molecular data are available for those cultivars of P. vulgaris with drought tolerance attributes. Results As a first approach, Pinto Saltillo (PS), Azufrado Higuera (AH), and Negro Jamapa Plus (NP) were assessed phenotypically and physiologically to determine the outcome in response to drought on these common bean cultivars. Based on this, a Next-generation sequencing approach was applied to PS, which was the most drought-tolerant cultivar to determine the molecular changes at the transcriptional level. The RNA-Seq analysis revealed that numerous PS genes are dynamically modulated by drought. In brief, 1005 differentially expressed genes (DEGs) were identified, from which 645 genes were up-regulated by drought stress, whereas 360 genes were down-regulated. Further analysis showed that the enriched categories of the up-regulated genes in response to drought fit to processes related to carbohydrate metabolism (polysaccharide metabolic processes), particularly genes encoding proteins located within the cell periphery (cell wall dynamics). In the case of down-regulated genes, heat shock-responsive genes, mainly associated with protein folding, chloroplast, and oxidation-reduction processes were identified. Conclusions Our findings suggest that secondary cell wall (SCW) properties contribute to P. vulgaris L. drought tolerance through alleviation or mitigation of drought-induced osmotic disturbances, making cultivars more adaptable to such stress. Altogether, the knowledge derived from this study is significant for a forthcoming understanding of the molecular mechanisms involved in drought tolerance on common bean, especially for drought-tolerant cultivars such as PS.